Optimal Degree of Balloon-Expandable Transcatheter Valve Oversizing in Patients With Borderline Aortic Annulus Measurements: Insights From a Multicenter Real-World Experience. (21st March 2023) - Panagides, Vassili; Cheema, Asim N.; Urena, Marina; Nombela-Franco, Luis; Veiga-Fernandez, Gabriela; Vilalta, Victoria; Regueiro, Ander; Del Val, David; Asmarats, Lluis; del Trigo, Maria; Serra, Vicenç; Munoz-Garcia, Antonio; et al.
Abstract : Background: The potential benefit of using larger or smaller transcatheter heart valves (THV) in patients with borderline aortic annulus measurement (BAM) remains uncertain. The objective of this study was to evaluate the clinical outcomes associated with the selection of larger or smaller THV in the context of BAM. Methods: This was a multicenter observational study including patients who underwent transcatheter aortic valve replacement with the SAPIEN 3 or SAPIEN 3 Ultra-valve systems (Edwards Lifesciences, Irvine, CA) from April 2014 to June 2021. BAM was defined according to the manufacturer sizing chart and included the following annulus areas: 314 to 346, 400 to 430, 500 to 546 mm 2 . A 1:1 propensity score matching was used to compare outcomes of patients with larger or smaller THV. Results: From a total of 2467 patients, BAM was identified in 852 patients (34.5%). A larger and smaller THV was selected in 338 (39.7%) and 514 patients (60.3%) patients, respectively. The choice of a larger THV was associated (before and after propensity matching) with a higher risk of new-onset left bundle branch block (HR, 2.25 [95% CI, 1.39–3.65; P =0.001) and permanent pacemaker implantation (HR, 1.86 [95% CI, 1.11–3.09]; P =0.016) without any impact on gradients or the risk of moderate or severe paravalvular regurgitation at discharge (HR, 0.78 [95% CI, 0.41–1.45]; P =0.427). The risk of periprocedural complications such as aortic rupture and tamponade was low (<1%) and similar between groups. Conclusions: In patient with BAM, selecting a larger SAPIEN 3/Ultra THV increased the risk of conduction disturbances without any benefit on valve hemodynamics and clinical outcomes.